2012
DOI: 10.1093/cid/cis933
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Attributable to Smoking Among HIV-1–Infected Individuals: A Nationwide, Population-Based Cohort Study

Abstract: In a setting where HIV care is well organized and antiretroviral therapy is free of charge, HIV-infected smokers lose more life-years to smoking than to HIV. The excess mortality of smokers is tripled and the population-attributable risk of death associated with smoking is doubled among HIV patients compared to the background population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
301
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(322 citation statements)
references
References 30 publications
17
301
0
4
Order By: Relevance
“…While opportunistic respiratory infections associated with advanced immunosuppression dominated the initial clinical picture in the setting of HIV infection, latterly, with the use of HAART, there has been a rise in deaths related to non-AIDS-defining illnesses, largely driven by the high rate of smoking among these individuals [15,18]. In fact, in those areas where HIV care is well organised and HAART is freely available, HIV-infected smokers lose more life-years to smoking than to HIV infection per se, the risk being considerable and often attributable to non-AIDS-defining conditions [12,15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…While opportunistic respiratory infections associated with advanced immunosuppression dominated the initial clinical picture in the setting of HIV infection, latterly, with the use of HAART, there has been a rise in deaths related to non-AIDS-defining illnesses, largely driven by the high rate of smoking among these individuals [15,18]. In fact, in those areas where HIV care is well organised and HAART is freely available, HIV-infected smokers lose more life-years to smoking than to HIV infection per se, the risk being considerable and often attributable to non-AIDS-defining conditions [12,15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Excess mortality due to smoking has also been shown among patients with other diseases, such as HIV. A study in Denmark indicated that mortality due to smoking is greater than mortality attributable to HIV among people with HIV/AIDS, showing that the number of life years lost due HIV was 5.1, compared to 12.3 because of smoking 4 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Furthermore, recent studies have shown that the population-attributable risk of death associated with smoking is higher (61.5%) among HIV-positive patients compared to controls (34.2%), postulating that in this particular category or patients, more life-years are lost to smoking than to HIV. 25 Despite an implementation of policies for reducing tobacco use, smoking continues to be a major issue in Romania. Having signed the World Health Organization (WHO) Framework Convention on Tobacco Control in 2004, with subsequent ratification in 2006, Romania has since made it on the list of highest achieving countries for monitoring the prevalence of tobacco use, tobacco dependence treatment and raising taxes on tobacco.…”
Section: Discussionmentioning
confidence: 99%